Theoretical Studies of Design Parameters of Machine Elements for Surface Planting of Rice - Masienko Ivan (EDP Sciences, 2021)
The paper presents the definition of the main parameters and operating modes of spreading centrifugal devices of technical means when using them in the surface planting technology. It has been determined analytically and experimentally that under the existing operating modes of centrifugal apparatus, in order to reduce reflection, grooved blades should be used, the upper planes of which are tilted from the horizontal position by an angle of 5-10 °, the angle of the blades should be ≤15 °. According to the results of theoretical and experimental studies, a prototype was made, the productivity of which when sowing rice in comparison with serial machines increased by 1.5 times with an uneven distribution over the working width not exceeding 15%.